2018
DOI: 10.1371/journal.pone.0193787
|View full text |Cite
|
Sign up to set email alerts
|

Automatic approach-avoidance tendencies as a candidate intermediate phenotype for depression: Associations with childhood trauma and the 5-HTTLPR transporter polymorphism

Abstract: Depression risk genes in combination with childhood events have been associated with biased processing as an intermediate phenotype for depression. The aim of the present conceptual replication study was to investigate the role of biased automatic approach-avoidance tendencies as a candidate intermediate phenotype for depression, in the context of genes (5-HTTLPR polymorphism) and childhood trauma. A naturalistic remitted depressed patients sample (N = 209) performed an Approach-Avoidance Task (AAT) with facia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 78 publications
2
6
0
Order By: Relevance
“…European studies are similar to the others, as they also found a higher frequency of the SL genotype [32]. By analyzing Dutch individuals' genotypes, Fleurkens et al [22] noted that 52% (n = 109) of the research participants had the La/Lg genotype. In another German study by Schneider et al [28], however, had the La/Sa genotype, a result similar to the study conducted in a Canadian population [39,40].…”
Section: Httlpr Variant Genotypic Distribution In the Populationsupporting
confidence: 59%
See 2 more Smart Citations
“…European studies are similar to the others, as they also found a higher frequency of the SL genotype [32]. By analyzing Dutch individuals' genotypes, Fleurkens et al [22] noted that 52% (n = 109) of the research participants had the La/Lg genotype. In another German study by Schneider et al [28], however, had the La/Sa genotype, a result similar to the study conducted in a Canadian population [39,40].…”
Section: Httlpr Variant Genotypic Distribution In the Populationsupporting
confidence: 59%
“…Although not finding a genotypic association of the present gene with childhood adversity (p = 0.128), depressed S/Lg genotype patients with childhood trauma, compared to those with the La/La genotype, avoided sad facial expressions, even after having their depressive and anxiety symptoms controlled. Furthermore, the S/Lg heterozygous group had less emotional and psychological resilience than the La/La homozygous group; that is, they were less able to deal with their problems, overcome obstacles and resist pressure, whether emotional or psychological [22].…”
Section: Httlpr Variant and Mdd Risk Factorsmentioning
confidence: 98%
See 1 more Smart Citation
“…Nevertheless, the current findings provide further evidence for the connection between 5-HTTLPR variation and biased processing of negative information. An interesting literature is emerging which appears to link the 5-HTTLPR to a range of negative cognitive biases (for a review, see [ 12 , 46 48 ], although one should keep in mind that publication bias is likely influencing this literature and meta-analyses likely overestimate the true association between the 5-HTTLPR and negative information processing biases. However, it is important to note that the 5-HTTLPR was not globally associated with negative cognitive bias in the current study, as there was no direct link with biased memory for affective stimuli in either study.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the current findings provide further evidence for the connection between 5-HTTLPR variation and biased processing of negative information. An interesting literature is emerging which appears to link the 5-HTTLPR to a range of negative cognitive biases (for a review, see [12,[46][47][48], although one should keep in mind that publication bias is likely influencing this literature and meta-analyses likely overestimate the true association between the 5-HTTLPR and negative information processing biases. However, it is important to note that the 5-HTTLPR was not globally associated with negative cognitive bias in the current study, as there was no direct link with biased memory for affective stimuli in either study.…”
Section: Discussionmentioning
confidence: 99%